Ações artísticas públicas: superfícies urbanas em aderência híbrida - Souza, Mariana Binato de (2016)
Permeating analog and digital processes, this project addresses a poetic production in visual arts in the field of art and technology, which is a proposal for interventions in urban areas, with the thematic territory and inner cities elements. The study, in this regard, seeks to approach the public and urban art of rural communities, places that are, in many instances, on the fringes of contemporary artistic manifestations, usually concentrated in the major urban centers. Thus, such public artistic actions, proposals to be shared collectively and collaboratively with the group involved, with respect to its constitution as a project, they are created from the interaction and collaboration of participants, allowing that the experenciados processes instigate new modes of subjectivity of the individual in his relationship with art in the present context.